Resting-state connectivity of the amygdala is altered following Pavlovian fear conditioning - Schultz, Douglas H.; Balderston, Nicholas L.; Helmstetter, Fred J. (Frontiers in Human Neuroscience, 2012)
Neural plasticity in the amygdala is necessary for the acquisition and storage of memory in Pavlovian fear conditioning, but most neuroimaging studies have focused only on stimulus-evoked responses during the conditioning session. This study examined changes in the resting-state functional connectivity (RSFC) of the amygdala before and after Pavlovian fear conditioning, an emotional learning task. Behavioral results from the conditioning session revealed that participants learned normally and FMRI data recorded during learning identified a number of stimulus-evoked changes that were consistent with previous work. A direct comparison between the pre and post-conditioning amygdala connectivity revealed a region of dorsal prefrontal cortex (PFC) in the superior frontal gyrus that showed a significant increase in connectivity following the conditioning session. A behavioral measure of explicit memory performance was positively correlated with the change in amygdala connectivity within a neighboring region in the superior frontal gyrus. Additionally, an implicit autonomic measure of conditioning was positively correlated with the change in connectivity between the amygdala and the anterior cingulate cortex. The resting-state data show that amygdala connectivity is altered following Pavlovian fear conditioning and that these changes are also related to behavioral outcomes. These alterations may reflect the operation of a consolidation process that strengthens neural connections to support memory after the learning event.